2017
DOI: 10.18632/oncotarget.23262
|View full text |Cite
|
Sign up to set email alerts
|

MiR-27a as a predictor for the activation of hepatic stellate cells and hepatitis B virus-induced liver cirrhosis

Abstract: Circulating microRNAs (miRNAs) can be employed as biomarkers to diagnose liver and other diseases. Noninvasive approaches are needed to complement and improve the current strategies for screening for biomarkers liver cirrhosis. We determined whether the serum levels of miRNAs can distinguish between chronic hepatitis B (CHB) and CHB-induced cirrhosis (HBC) and investigated the potential mechanisms involved. We found that serum miR-27a was significantly up-regulated in HBC, distinguishing HBC from CHB and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…For example, TGF-β activation of HSCs can downregulate miR-29b that then fails to modulate the expression of collagen [117] (see Schematic 4,pathway 19). TGF-β1-activated HSCs also enhance the expression of miR-27a, which suppresses antagonists of α-SMA and collagen like PPARϒ, FOXOI, APC, p53, and RXRα to promote fibrogenesis [118] (see Schematic 4,pathway 20). Schematic 4, HBx-mediated fibrosis/cirrhosis pathways.…”
Section: Mirna Regulating Hbv-induced Fibrosis/cirrhosismentioning
confidence: 99%
“…For example, TGF-β activation of HSCs can downregulate miR-29b that then fails to modulate the expression of collagen [117] (see Schematic 4,pathway 19). TGF-β1-activated HSCs also enhance the expression of miR-27a, which suppresses antagonists of α-SMA and collagen like PPARϒ, FOXOI, APC, p53, and RXRα to promote fibrogenesis [118] (see Schematic 4,pathway 20). Schematic 4, HBx-mediated fibrosis/cirrhosis pathways.…”
Section: Mirna Regulating Hbv-induced Fibrosis/cirrhosismentioning
confidence: 99%
“…e human hepatocyte L02 cell line was purchased from the Cell Bank of Chinese Academy of Sciences (Shanghai, China). Cell culture conditions and cell treatments were as previously described [26]. Exponentially growing LX2 cells were treated with 10 ng/ml TGF-β1 (R&D Systems, Shanghai, China) for 24 h or 48 h, and then cells were collected for miRNA isolation and RT-qPCR analysis.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…Analysis. RNA isolation and quantitative real-time RT-PCR (RT-qPCR) was carried out as previously described [26]. Primers for miR-663a and U6 (RT-qPCR Primer Set) were purchased from Guangzhou RuiBio Corp. (Guangzhou, China).…”
Section: Rna Isolation and Quantitative Real-time Rt-pcrmentioning
confidence: 99%
“…Several studies have shown that miR-27a is overexpressed in liver stellate cells, influencing fat accumulation and cell proliferation, leading to hepatic fibrosis (83). It was also proven that miR-27a can induce liver fibrosis and be used as a diagnostic biomarker in advanced liver fibrosis and cirrhosis with hepatitis viruses B and C (84).…”
Section: Mir-27a In Promoting Tumorigenesismentioning
confidence: 99%